NOTCH1 is a mechanosensor in adult arteries. Issue 1 (December 2017) - Mack, Julia; Mosqueiro, Thiago; Archer, Brian; Jones, William; Sunshine, Hannah; Faas, Guido; Briot, Anais; Aragón, Raquel; Su, Trent; Romay, Milagros; McDonald, Austin; Kuo, Cheng-Hsiang; et al.
Abstract Endothelial cells transduce mechanical forces from blood flow into intracellular signals required for vascular homeostasis. Here we show that endothelial NOTCH1 is responsive to shear stress, and is necessary for the maintenance of junctional integrity, cell elongation, and suppression of proliferation, phenotypes induced by laminar shear stress. NOTCH1 receptor localizes downstream of flow and canonical NOTCH signaling scales with the magnitude of fluid shear stress. Reduction of NOTCH1 destabilizes cellular junctions and triggers endothelial proliferation. NOTCH1 suppression results in changes in expression of genes involved in the regulation of intracellular calcium and proliferation, and preventing the increase of calcium signaling rescues the cell–cell junctional defects. Furthermore, loss ofNotch1 in adult endothelium increases hypercholesterolemia-induced atherosclerosis in the descending aorta. We propose that NOTCH1 is atheroprotective and acts as a mechanosensor in adult arteries, where it integrates responses to laminar shear stress and regulates junctional integrity through modulation of calcium signaling. The arterial wall is subjected to mechanical forces that modulate endothelial cell responses. Here, Mack and colleagues identify a novel role for Notch1 as a mechanosensor in adult arteries, where it ensures junctional integrity through modulation of calcium signalling and limits atherosclerosis.